Seasonality of agricultural exposure as an important predictor of seasonal yellow fever spillover in Brazil - Arran Hamlet (Nature Portfolio, 2021)
Yellow fever virus (YFV) is an arbovirus affecting humans and non-human primates (NHPs) with seasonal transmission. Here Hamlet et al. model the monthly occurrence of YF in humans and NHPs across Brazil and show that seasonality of agriculture is an important predictor of seasonal YF transmission.